Concomitant production of delta-endotoxins and proteases of Bacillus thuringiensis subsp. kurstaki in a low-cost medium : effect of medium components - Ennouri, Karim (Acta Biologica Szegediensis, 2013)
Bacillus thuringiensis is a bacterium, commonly used as a biological pesticide, and produces entomotoxic parasporal crystals (delta-endotoxins) and photolytic enzymes involved in several biological processes. The aim of present work was to enhance the production of delta-endotoxins by an isolated Bacillus thuringiensis subsp. kurstaki strain. The adopted approach was based on studying both delta-endotoxins and proteolytic activities production. Trials were carried out based on the Plackett-Burman experimental design. The statistical analysis revealed that the soybean meal was the main significant ingredient (confidence level= 99.5%) for both delta-endotoxins and proteolytic activities productions. Starch and FeSO4 were considered as significant ingredients for only protease production, the confidence levels were 98.8% and 97% respectively. The study of the nutrients effects brought out that K2HPO4, FeSO4 and starch, exhibit an opposite effect on the synthesis of delta-endotoxins and proteolytic activity production. On the other hand, MnSO4, MgSO4 and soybean meal are considered as the ingredients having dual positive effect on proteolytic activities and delta-endotoxin productions, whereas KH2PO4 had an inhibitory effect. The optimisation strategy using mathematical methods offers an efficient technique to optimize media leading to the increase delta-endotoxin production by Bacillus thuringiensis subsp. kurstaki strains by clustering of the effects of medium components.